Mediasi Penal Sebagai Alternatif Penyelesaian Perkara Kecelakaan Lalu Lintas di POLRES Pasuruan - Eko Iskandar* (Universitas Airlangga, 2017)
In Pasuruan Regional police station amount of accidents in 2018 has decreased, but amount of dead victims still relatively high. In 2018 there 533 events, in 2017 there 809 events and 2016 there 908 events, if on average there 756 events in the last 3 years. The majority of settlement the case uses the mediation of penal process. So the authors interested in researching the basis of the implementation of penal mediation as an alternative to the settlement of cases in traffic accidents in Pasuruan Regional Police and the obstacles the implementation of traffic accident settlement through mediation penalties. The method in this study uses a qualitative approach data collection techniques through interviews and documentation studies. Data analysis techniques based on data collection, data reduction, data display verification and confirmation of conclusions. The basis of implementation the mediation of law, among others, legal basis and sociological basis The juridical basis used includes the authority to